Konsep Nafsu Dalam Kontruksi Cerita Dewaruci - Fajriatul Mustakharoh (Jurusan Tasawuf dan Psikoterapi Fakultas Ushuluddin, Adab dan Dakwah UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
Javanese society is known to be very symbolic, having an extraordinary way of meaning and conveying its moral-ethical teachings. This is inseparable from the rich combination of values ​​recorded in history that have helped shape the personality of the Javanese people. One of the most significant influences is Islam, which was brought and buried by Walisongo through a very humanist-innovative-creative process of Islamization, thus making Islam embraced without going through an expansive path that is sometimes intimidating. The media chosen was wayang with an extraordinary storyline modification so that it could bring the Javanese people lighter and entertained in understanding Islamic values. Meanwhile, Dewaruci's story is a good example of how Walisongo explained the concept of lust to ordinary Javanese people at that time. This research includes library research using descriptive analysis. The data is obtained by reviewing, tracing, documenting, describing and analyzing the required literature. The results of this study indicate that Bima's meeting with the five Bayu who were none other than himself, then was able to bring him to Dewaruci. Dewaruci itself is the personification of sangkan paraning dumadi (the place of origin of creation) which symbolizes the authenticity and purpose of life, namely Allah SWT.